Voices of Shame: Female Characters in Selected Works by Bina Štampe Žmavc, Polonca Kovač and Špela Frlic - Zajc, Ivana (Trideset let literarne nagrade večernica, 2026)
This article examines contemporary Slovenian children's literary works by Bina Štampe Žmavc, Polonca Kovač, and Špela Frlic, all recipients of the Večernica Award: Cesar in roža (The Emperor and the Flower), Kaja in njena družina (Kaja and Her Family), and Bleščivka (The Glittering One). The focus is on texts intended for younger readers, in which shame constitutes an important yet often indirectly expressed experience. The works are analyzed through the lens of the emotion of shame and the narratological category of voice, understood as a textual effect related to style and subjectivity (Aczel, 1998). The analysis shows that shame appears in connection with family relationships, social exclusion, poverty, and moral transgressions. Focusing on female characters, it demonstrates how children's literature creates space for reflection on vulnerability and exclusion. Particular attention is given to the question of who shames and who experiences shame, as well as to the phenomenon of unspoken emotions, manifested in the absence of voice among certain characters. The concluding section of the article offers several starting points for addressing the emotional dimensions of literary texts in educational practice.